Prognostic value of preoperative alpha-fetoprotein (AFP) level in patients receiving curative hepatectomy- an analysis of 1,182 patients in Hong Kong - Chan, Miu Yee; She, Wong Hoi; Dai, Wing Chiu; Yin Tsang, Simon Hing; Ho Chok, Kenneth Siu; Yan Chan, Albert Chi; Fung, Jame; Lo, Chung Mau; Cheung, Tan To (Translational Gastroenterology and Hepatology; Vol 4 (July 2019): Translational Gastroenterology and Hepatology, 2019)
Background: The value of alpha-fetoprotein (AFP) as a prognostic indicator in patients with hepatocellular carcinoma (HCC) has been proposed in recent studies, but the evidence so far is still contradictory. This analysis aims to evaluate the prognostic value of preoperative AFP level in patients undergoing curative resection. Methods: This retrospective study reviewed the prospectively collected data of all patients who underwent initial liver resection for HCC at Queen Mary Hospital during the period from March 1999 to March 2013. Patients with palliative resection, positive margin after pathological examination or distant metastasis were excluded from the study. Survival of patients with AFP level of 400 ng/mL were compared with Kaplan-Meier analysis. Subgroup analysis was performed according to tumour stage (7th edition UICC staging) and tumour size. The optimal cutoff value was determined by area under receiver operating characteristic curve. Results: A total of 1,182 patients were included. Best overall (OS) and disease free survival (DFS) was observed in patients with AFP level